Normative and descriptive models for COBie implementation: discrepancies and limitations. Issue 8 (16th September 2019) - Abdirad, Hamid; Dossick, Carrie S.
Abstract : Purpose: The purpose of this paper is to inquire into the reasons why Construction Operation Building Information Exchange (COBie) has not become mainstream across the construction industry despite the significant attempts to promote it. Design/methodology/approach: This paper framed and compared the normative model of COBie to a descriptive model of COBie. The normative model was based on the assumptions and planned procedures outlined in the COBie documentation. The descriptive model was developed through a case study of COBie implementation, with ethnographic observations, interviews and artifact analysis as the data collection methods and thematic analysis as the data analysis method. Findings: The comparative analysis of the normative and descriptive models showed that the underlying normative assumptions of COBie can be challenged in its implementation. In the case study, implementing COBie disrupted the conventional practice of few participating firms as the data requirements and the expected sequences and timelines of tasks were not aligned with the industry norms for exchanging data. Furthermore, the normative model of COBie could not account for the unanticipated variability in the internal routines of firms for submittal production. Practical implications: COBie, as an instruction-based model, may not provide enough flexibility for some firms to adapt to its requirements such that COBie tasks become integrated with their existing workflows. COBie tasks may become additional efforts, and at times, conflict with the industry norms and firms' routines, and therefore, disrupt the efficiency goals. Originality/value: This paper provides empirical evidence to clarify why implementing COBie has not been as efficient for all industry players as expected.